TINDAK UJAR KONVIVIAL DALAM FILM HUNGER GAMES â€œMOCKINGJAYâ€ KARYA FRANCIS LAWRENCE ( SUATU ANALISIS PRAGMATIK ) - NGANTUNG, ANATASYA; JANSEN, FRIEDA TH.; LOTULUNG, DONALD R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTConvivial act as a part of Illocutionary is not only found in our daily life, but also in literary studies such as novel, drama, short stories, novella and film. This study is an attempt to identify, classify Â and analyze the aspect of convivial act in the film Hunger Games : Mockingjay directed by Francis Lawrence. The method used in the research is descriptive method. The data are identified and analyzed descriptively. In collecting data, the writer reads some pragmatic books pertaining to convivial act. After that, the writer watches the film and looks the whole story of the film to obtain good understanding of the context of the story inthe film.Then the writer identified and classified the data into relevant aspects of convivial act. The collected data were analyzed descriptively in terms of how the aspect of convivial are found in the film Hunger Games : Mockingjay based on Leechâ€™s and Austin theory. The research show that the convivial act can be categorized into five categories, those are offering, inviting, greeting, congratulating, and thanking, and how the aspect of convivial act used by the characters. It is expected that this study will help students and readers In learning pragmatics especially on convivial aspects found in the film.__________________Â___________________Keywords : Convivial Act, Film : Hunger Games : Mockingjay, Pragmatic AnalysisÂ